Factors of stress influence performance of works civil defence department’s staffs in Kelantan at Kelantan Civil Defence’s Administration Department / Suhana Yunus - Yunus, Suhana (2011)
This research attempted to identify the factors that influence the performance of works Civil Defence Department‟s staffs in Kelantan and also to assess whether there are significant difference some demographic variables on performance of staffs‟.Researcher conducted this research since there are a complaint about declining in performance of works Civil Defence Department.In this study researcher use self administered questionnaire to gather the data from Kelantan Civil Defence Department‟s staffs as respondents.The questionnaire have been distributed about 120 set to district and unit‟s office.The dependent variable is performance of works Civil Defence Department‟s staffs in Kelantan and independent variables are organization(x1),workplace(x2),environment(x3) and personal(x4).This study consist eight hypotheses to be analyzed,two research questions and two objectives to achieve.There are 120 staffs in all offices,researcher collected about only 114 respondents answered the questionnaire completely.The sampling method used is simple random sampling.For analyzing the data researcher used software SPSS 18 and some of the test that researcher used in this study are normality of data,measure skewness,F test and reliability analysis.The findings of the study shows that factor of stress that influence the performance of works Civil Defence Department‟s staffs are workplace,environment and personal stress.This study also found that there are significant difference marital status on performance of works Civil Defence Department‟s staffs